PEMBERDAYAAN K’CAK COFFEE DENGAN PENGEMBANGAN INTELLECTUAL CAPITAL, TATA KELOLA KEUANGAN DAN MARKET PLACE - Mimba, N.P.S.H.; Ratnadi, N.M.D.; Sudana, I.P.; Wirakusuma, M.G. (Buletin Udayana Mengabdi, 2024)
This community service activity aims to empower the K'Cak Coffee business. A preliminary study conducted by the service team found that the K'Cak Coffee business has high potential for development, however this business is still facing several problems, especially problems related to intellectual capital management. The first problem is related to production problems, namely product packaging which is not optimal in maintaining product durability because it does not use a vacuum machine. The second problem faced by K'Cak Coffee is related to financial management and governance, this is due to limited knowledge of human resources and human capital management in the financial sector. Another problem faced by K'Cak Coffee is marketing that has not utilized marketplace or e-commerce technology so that product marketing reach is still not optimal. Before carrying out the service, the service team will coordinate with partners and village officials. This service is carried out in several stages of socialization and training according to the problems faced by K'Cak Coffee by presenting resource persons and involving Catur Village KKN students. The results of this service are increasing partners' skills in using vacuum machines, increasing knowledge related to financial management and governance, partners are able to become familiar with marketing technology and knowledge related to expanding marketing networks with e-commerce as well as providing information related to export potential. Keywords: Catur Village, E-commerce, Intellectual Capital, K'Cak Coffee, Marketplace.This community service activity aims to empower the K'Cak Coffee business. A preliminary study conducted by the service team found that the K'Cak Coffee business has high potential for development, however this business is still facing several problems, especially problems related to intellectual capital management. The first problem is related to production problems, namely product packaging which is not optimal in maintaining product durability because it does not use a vacuum machine. The second problem faced by K'Cak Coffee is related to financial management and governance, this is due to limited knowledge of human resources and human capital management in the financial sector. Another problem faced by K'Cak Coffee is marketing that has not utilized marketplace or e-commerce technology so that product marketing reach is still not optimal. Before carrying out the service, the service team will coordinate with partners and village officials. This service is carried out in several stages of socialization and training according to the problems faced by K'Cak Coffee by presenting resource persons and involving Catur Village KKN students. The results of this service are increasing partners' skills in using vacuum machines, increasing knowledge related to financial management and governance, partners are able to become familiar with marketing technology and knowledge related to expanding marketing networks with e-commerce as well as providing information related to export potential. Keywords: Catur Village, E-commerce, Intellectual Capital, K'Cak Coffee, Marketplace.